THE STUDY OF ENGLISH WORD FORMATION INBRING IT ON 3: All or Nothing and Stealth Movie Scripts - Irni Diniati, - (2008)
The research entitled The Study of English Word Formation in Bring it on 3: All or Nothing and Stealth Movie Scripts is aimed to reveal the acronym, blend~d ipping words as well as to identify the context of situation leadin o the use of those words in two movie scripts reflecting the situation o ilitary and high school. The data source is two movie scripts entitled Bring it on 3: All or Nothing and Stealth. From those movie scripts, the data were transcribed and then analyzed based on O'Grady's word formation types and Hymes' SPEAKING approach. The result of the analysis shows that there are some acronym, blend and clipping tokens , found in both movie scripts. Some of them are BFF, AAA, cheer-ocracy, warplane, caf and beacon. Furthermore, the context of situation leading to the use each tokens is various whether it is used between friends, colleagues or among superior-subordinate, within both formal and informal situations.